2019
DOI: 10.3390/electronics8010086
|View full text |Cite
|
Sign up to set email alerts
|

Hyperspectral Image Denoising Based on Spectral Dictionary Learning and Sparse Coding

Abstract: Processing and applications of hyperspectral images (HSI) are limited by the noise component. This paper establishes an HSI denoising algorithm by applying dictionary learning and sparse coding theory, which is extended into the spectral domain. First, the HSI noise model under additive noise assumption was studied. Considering the spectral information of HSI data, a novel dictionary learning method based on an online method is proposed to train the spectral dictionary for denoising. With the spatial–contextua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…The SR algorithm is based on the principle of representing the signal with as few atoms as possible in a given super-complete dictionary, which means that the denoised spectrum must have some loss of information compared to the spectrum before denoising. Although the SR algorithm removes some of the high-frequency noise, the process of removing the noise takes away some of the valid information, making the denoised signal less similar to the original signal waveform [21,48,49].…”
Section: Construction Of Prediction Models For CL Nitrogen Contentmentioning
confidence: 99%
“…The SR algorithm is based on the principle of representing the signal with as few atoms as possible in a given super-complete dictionary, which means that the denoised spectrum must have some loss of information compared to the spectrum before denoising. Although the SR algorithm removes some of the high-frequency noise, the process of removing the noise takes away some of the valid information, making the denoised signal less similar to the original signal waveform [21,48,49].…”
Section: Construction Of Prediction Models For CL Nitrogen Contentmentioning
confidence: 99%
“…Thus, to handle this issue, recent HSI denoising methods, jointly considering the preservation of spatial and spectral information, directly treat the HSI as a 3D data cube for modeling from the perspective of better exploring image priors, such as non-local self-similarity across space (NSS) (Nonlocal self-similarity (NSS) across space is to explore the spatial similarity among image patches (even pixels). ), global correlation along spectral (GCS) Global correlation along spectral (GCS) mainly focuses on depicting the relationship among features along spectral direction [12,13], low-rank tensors [9,14], sparse coding [32][33][34], etc. [35].…”
Section: Related Workmentioning
confidence: 99%
“…Mineral mapping experiments with noise-reduced AVIRIS and Hyperion HSIs demonstrate the algorithm's effectiveness and advancement in denoising performance. After using an online dictionary learning method to train the spectral dictionary, Literature [12] conceptualizes a method for denoising by taking into account HIS spectral information. Based on the test, it is confirmed that the proposed method's denoising effect is 1 dB more powerful than the conventional method's.…”
Section: Introductionmentioning
confidence: 99%